The sustainable engineering of continuous hydrothermal synthesis - Caramazana Gonzalez, Pablo (2017)
Nanomaterials are increasingly used in novel applications, devices and processes. As a result industrial scale production it is a growing area. Continuous-flow hydrothermal synthesis (CFHS) offers substantial advantages over conventional techniques that can manufacture nanomaterials, due to its potential scalability from laboratory to industrial plant, versatility to synthesize a large variety of nanomaterials and its simplicity. Also, increasing concern around the environmental impact of manufacturing processes has led to the development of more careful and sustainable strategies from industry. As such, CFHS represents a clear alternative by using water as solvent, with shorter reaction times and low manufacturing temperatures compared with other synthesis routes. This thesis assesses the life cycle environmental impact of CFHS at industrial scale for a wide range of nanomaterials. In general, the evaluation involves the production of the nanoparticles (“cradle-to-gate”), considering various operational parameters and conditions such as scale, precursor type, reaction temperature and operational configuration. The recent industrial plant built in Nottingham is used to provide essential data for the life cycle assessment (LCA). Chapter 4 specifically assesses the impact of scale-up of lithium iron phosphate (LFP) nanoparticles production from laboratory and pilot scale to the industrial plant. The influence of more concentrated precursor solutions and lower production yield is also evaluated in the case of industrial scale, allowing a wider comparison of alternative LFP production methods with CFHS. Chapter 5 combines practical experiments to model LCA of the industrial production. A set of experiments were carried out to produce titanium dioxide (TiO2 or titania) nanoparticles in the laboratory, using different titanium precursors at a range of different reaction temperatures. The characteristics of each sample were used to determine the relations between quality and yield at industrial scale as well as the environmental impact of each scenario. This chapter presents a detailed and useful basis for any future production of titania nanoparticles using CFHS. Chapter 6 and 7 evaluate the tribological performance of ten metal sulfides nanoparticles (nano-sulfides) as lubricant additives in water and pure mineral oil. To do this, silver sulfide was synthesized for the first time using CFHS (Chapter 6) alongside a range of other nano metal sulphides. The industrial production of five lubricants (formed by nanoparticles at 5wt% in mineral oil) was also evaluated in order to determine the life cycle impact of their production. This assessment quantified the impact of three synthesis configurations, two reaction temperatures and four metal salt precursors. Overall, it has been proven that CHFS is able to produce a large variety of nanomaterials with different chemical compositions, including phosphates, metal oxides and metal sulfides, achived by varying the operational conditions such as temperature or precursor choice. The scale-up of this technique (carried out during the SHYMAN project) has led to a reduction of the overall environmental impact of production due to the optimization of the process and the higher productivity of the plant. Finally, CFHS has resulted in lower environmental impact than other existing and emerging techniques for the production of nanomaterials such as sol-gel, pyrolysis, plasma, Altair process or batch hydrothermal or solvothermal synthesis.